A review of tribological properties for boron carbide ceramics - Zhang, Wei (Progress in Materials Science, 2021)
B4C has characteristics of low density, good strength, good wear resistance, exceptional hardness, high elastic modulus and good chemical inertness at room temperature. Therefore, B4C ceramics are considered as potential candidates for tribological applications. However, the poor friction property, which can cause a lot of energy consumption during friction process, limits the extensive application of B4C ceramics in the filed of wear resistance. In this review, the current research progress regarding tribological properties of B4C ceramics is systematically reviewed. The relevant strategies to improve the tribological properties, including microstructures, mechanical properties, surface characteristics, self-lubrication and external factors, are comprehensively discussed. The tribological properties of B4C ceramics under lubrication conditions and tribochemical reactions of B4C ceramics are also presented. Finally, future directions of B4C ceramics in the field of tribology are proposed. This review aims to provide some meaningful guidelines for tribologists on the future study of B4C ceramics with low friction and low wear.